Complacência e sensibilidade retal no pré e pós-operatório de pacientes com hemorróidas tratados por anopexia mecânica - Albuquerque Filho, Francisco Leopoldo (2005)
Post-graduation Course in Surgery (Strictu Sensu), Departament of Surgery, Medicine School, Federal University of Ceará (Master in Surgery Degree). 2005, September. Professor: Prof. Dr. Lusmar Veras Rodrigues Surgical treatment of haemorrhoids by Stapled Anopexy (SA), using a circular stapler PPH® - 33mm (Ethicon EndoSurgery) may damage perianal muscle fibers, with changes In defecation pattern. The aim of this study was to evaluate rectal compliance and sensitivity in patients treated by SA. Ten patients with grade III or IV sintomatic haemorrhoids were elegible for this study. All patients were studied before surgery with a barostat (Visceral Stimulator; Synetics Medical), using two research protocols for rectal sensitivity: a continuous one (Ramp Test) and another one in steps (Random test), that could record patient's perception to volumetric distention of a rectal baloon, controled by a software (Polygram for Windows, Medtronic). This software made the method reproductible to all patients in the post-operative period. The barostat was able to record the first rectal sensation (1st. sensation), urge to defecate (2nd. sensation) and rectal pain (3rd. sensation). Patients were studied following the same protocol at two, four and six months after surgery. A control group of ten patients with pilonidal sinus disease was submitted to the same protocol, except for stapled anopexy. Statistical analysis was acomplished using Pearson and Student's t test. The study found a decrease in retal compliance and sensitivity of patients treated by stapled anopexy, during the second post-operative month evaluation, for all recorded sensations, to all distension protocols. There was no difference in rectal compliance and sensitivity between pre-operative and post-operative at four and six months evaluations for patients treated by stapled anopexy. There was no difference in rectal compliance and sensitivity for any patient in control group, for any sensation recordered, using any distension protocol. The conclusion was that stapled anopexy caused a transient decrease in rectal compliance and sensitivity at the second postoperative month, that returned to normal values at the fourth post-operative month.